Introducing ERP System as a Condition of Information Security and Accounting System Transformation - Trunina, Iryna; Vartanova, Olena; Sushchenko, Olena; Onyshchenko, Oksana (International Journal of Engineering and Technology, 2018)
Despite the level of the information technology spread in Ukraine being lower than in other countries ERP systems are introduced both on the levels of commercial and government organizations. Although there is an adaptation to the national and language features of different countries in ERP systems, their introduction into Ukrainian markets relates to a range of difficulties. Information safety issues and the issues of changes in management accounts and business accounting that appear when introducing ERP system are the main difficulties for Ukrainian enterprises. The research of information security considers such main aspects as the network security, the data base (DB) security, the security on the level of application server and the information security on the clientâ€™s computer. The determination of the main principles of the information security and the suggestion of the stages of building the ERP security control subsystem aim at preventing deliberate or accidental information leak. Features of Ukrainian legislation, differences of Ukrainian business accounting standards from the international ones and the management features should be considered when introducing ERP system. The company executives, in their turn, should understand the urgent need in introducing information technologies, realize that the information system is a management system and not only the system of accounting and should meet the requirements and standards of ERP management.Â Â